Addressing Climate Change in Local Water Agency Plans Demonstrating a Simplified Robust Decision Making Approach in the California Sierra Foothills - Groves, David G. (RAND Corporation, 2013)
This report describes an approach for planning under deep uncertainty, Robust Decision Making (RDM), and demonstrates its use by the El Dorado Irrigation District (EID). Using RDM, the authors and EID tested the robustness of current long-term water management plans and more robust alternatives across more than 50 futures reflecting different assumptions about future climate, urban growth, and the availability of important new supplies.